Conservative solute transport with periodic velocity and sinusoidal source concentration in semi-infinite porous media: An analytical solution - Yadav, R R; Gulrana, Gulrana; Jaiswal, Dilip Kumar (JOURNAL OF ADVANCES IN PHYSICS, 2014)
The present paper has been focused mainly towards understanding of the various parameters affecting the transport of conservative solutes in horizontally semi-infinite porous media. A model is presented for simulating one-dimensional transport of solute considering the porous medium to be homogeneous, isotropic and adsorbing nature under the influence of periodic seepage velocity. Initially the porous domain is not solute free. The solute is initially introduced from a sinusoidal point source. The transport equation is solved analytically by using Laplace Transformation Technique. Alternate as an illustration; solutions for the present problem are illustrated by numerical examples and graphs.